Parental Investment in Children's Human Capital in Urban China. - Yueh, L (2006)
The present study tests the extent of parental forgone consumption used instead to invest in children's human capital by use of intrahousehold resource allocation models. Using an unusual, comprehensive data set for urban China, there is more spending on boys aged 13 to 15 but more on girls aged 16 to 18, suggesting that standard human capital theories and traditional perceptions of gender bias do not completely explain educational expenditure decisions. The evidence from urban China is consistent, though, with human capital models which consider parental intertemporal preferences. Also, the findings suggest that the perceived bias in favour of sons exists weakly in contemporary urban China.